Analisis Implementasi Akad Qordh Dan Wakalah Bil Ujroh Dalam Pembiayaan Bank Syariah - Nurcahyati, Lina Dwi; Sanjayawati, Hilda (JPSDa: Jurnal Perbankan Syariah Darussalam, 2025)
Bank Muamalat is the first Islamic bank. By carrying the name of Sharia, Bank Muamalat implements the Islamic Sharia system with several contracts applied in it. Islamic Bank is a Bank that in carrying out its business activities is based on Sharia Principles and according to its type consists of Islamic Commercial Banks and Islamic. This study aims to determine and analyze the implementation of the qordh and wakalah bil ujroh contracts in financing. In order to achieve this goal, here the researcher uses a descriptive qualitative method. In collecting data, the study collected from several data sources such as interviews with related parties, namely sub-branch managers, academics representing universities and practitioners. And in this study reveals the facts of the incident, conditions and variables that occurred when this study was taking place by presenting what actually happened after carrying out a financing agreement properly and in its implementation it was in accordance with the rules of the DSN MUI. However, in this financing system there is something that is still lacking, namely in terms of officers marketing financing, because in terms of financing, the person in charge is relationship marketing funding, not relationship marketing landing.